Formulation and Characterization of Benzoyl Peroxide Gellified Emulsions - Thakur, Naresh Kumar (Österreichische Apotheker-Verlagsgesellschaft, 2012)
The present investigation was carried out with the objective of formulating a gellified emulsion of benzoyl peroxide, an anti-acne agent. The formulations were prepared using four different vegetable oils, viz. almond oil, jojoba oil, sesame oil, and wheat germ oil, owing to their emollient properties. The idea was to overcome the skin irritation and dryness caused by benzoyl peroxide, making the formulation more tolerable. The gellified emulsions were characterized for their homogeneity, rheology, spreadability, drug content, and stability. In vitro permeation studies were performed to check the drug permeation through rat skin. The formulations were evaluated for their antimicrobial activity, as well as their acute skin irritation potential. The results were compared with those obtained for the marketed formulation. Later, the histopathological examination of the skin treated with various formulations was carried out. Formulation F3 was found to have caused a very mild dysplastic change to the epidermis. On the other hand, the marketed formulation led to the greatest dysplastic change. Hence, it was concluded that formulation F3, containing sesame oil (6%w/w), was the optimized formulation. It exhibited the maximum drug release and anti-microbial activity, in addition to the least skin irritation potential.